Retrospective analysis of patients with placenta previa Plasenta previa olgularının retrospektif incelemesi - ÖZCAN, PINAR; BATMAZ, Gonca; DANSUK, RAMAZAN; MOLLA, Fulya; KILIÇOĞLU DANE, PAKİZER BANU; MOLLA, Taner; ÖZCAN, PINAR; Dansuk, RAMAZAN; Dane, Banu (My University, 2015)
Aim: To evaluate risk factors of patients with placenta previa and investigate management strategies. Methods: A retrospective review of medical records of 41 cases with placenta previa who were followed up in our center. The cases were evaluated according to demographic features, presence of placental invasion of the uterus, and necessity of blood transfusion. Requirement for a peripartum hysterectomy, relaparotomy rates and neonatal outcomes were also addressed. All patients with placenta previa were considered for elective surgery. Results: Eighteen patients, who did not have any sign of uterine invasion in their antenatal sonographic evaluations, were observed alike during cesarean section. In 23 patients, uterine invasion was detected by antenatal sonographic evaluations, 15 patients underwent hysterectomy due to invasion. Subsequent laparotomy was needed in four patients in whom hysterectomy was performed. Out of 15 patients, who underwent hysterectomy, 9 had placenta accreata, 2 had placenta percreata, and 2 had placenta increata. Organ-preserving treatment was performed in 8 patients who had a suspicious uterine invasion owing to their antenatal sonographic evaluations. Conclusion: In our study, abnormal placental invasion was predicted by antenatal sonographic findings. Multidisciplinary approach is required for patients with placenta previa to determine appropriate mode and timing of delivery.
Keywords: placenta previa